On Expulsions and Amnesties. Notes for a History of the Movement of Non-Tenured Professors (PNN) in (and from) the Universidad Autónoma de Madrid, 1968-1980 - Albarrán Diego, Juan (CIAN-Revista de Historia de las Universidades, 2025)
This article reconstructs part of the actions developed by the PNNs (non-tenured professors) at the Universidad Autónoma de Madrid (Autonomous University of Madrid, UAM) from the birth of the institution, in 1968, to the lecturers’ amnesties produced in the early 1980s. Some of the movement objectives were of a labor and corporate nature, such as improving their salaries, social security contributions or transparency in hiring processes. Others, however, were political, such as the democratization of academic life, increased investment in science, or criticism to the commercialization and privatization of higher education.
Keywords: antifrancoism; non-tenured professors; social movements; Transition; university